Human Milk-Based or Bovine Milk-Based Fortifiers Differentially Impact the Development of the Gut Microbiota of Preterm Infants - Aguilar-Lopez, Miriam; Wetzel, Christine; MacDonald, Alissa; Ho, Thao T. B.; Donovan, Sharon M. (Frontiers in Pediatrics, 2021)
Background: Preterm infants are exposed to different dietary inputs during their hospitalization in the neonatal intensive care unit (NICU). These include human milk (HM), with a human milk-based (HMF) or a bovine milk-based (BMF) fortifier, or formula. Milk consumption and the type of fortification will cause changes in the gut microbiota structure of preterm infants. This study aimed to characterize the gut microbiota of PT infant according to the type of feeding and the type of HM fortification and its possible association with infant’s growth. Methods: Ninety-seven infants born ≤33 wks of gestation or <1500 g were followed during the hospitalization period in the NICU after birth until discharge. Clinical and dietary information was collected, including mode of delivery, pregnancy complications, mechanical ventilation, use of antibiotics, weight, and type and amount of milk consumed. To characterize the gut microbiota composition, weekly stool samples were collected from study participants. The V3-V4 region of the 16S rRNA bacterial gene was sequence using Illumina MiSeq technology. Results: After birth, black maternal race, corrected gestational age (GA) and exposure to pregnancy complications, had a significant effect on gut microbial diversity and the abundance of Enterococcus, Veillonella, Bifidobacterium, Enterobacter and Bacteroides. Over the course of hospitalization, corrected GA and exposure to chorioamnionitis remained to have an effect on gut microbial composition. Two different enterotypes were found in the gut microbiota of preterm infants. One enriched in Escherichia-Shigella, and another enriched in uncharacterized Enterobacteriaceae, Klebsiella and Clostridium sensu stricto 1. Overall, HM and fortification with HMF were the most common feeding strategies. When consuming BMF, PT infants had higher growth rates than those consuming HMF. Milk and type of fortification were significantly associated with the abundance of Clostridium sensu stricto 1, Bifidobacterium and Lactobacillus. Conclusions: This observational study shows the significant association between milk consumption and the exposure to HMF or BMF fortification in the fecal microbiota composition of preterm infants. Additionally, these results show the effect of other perinatal factors in the establishment and development of PT infant’s gut microbiota.